The Consumption Level of Kalug Crickets (Gryllus bimaculatus) on Several Types of Local Vegetables in Palembang - Kurnia, Riza; Mutiara, Dian; Marmaini, Marmaini (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The research method utilized an experimental design with 6 treatments of local vegetable types: water spinach leaves (P1), spinach leaves (P2), cassava leaves (P3), sweet leaf leaves (P4), lettuce leaves (P5), and mustard greens (P6), replicated 5 times. The parameters observed were the weight of vegetables consumed (feed reduction) and the body weight growth of the crickets over 7 days. Data were analyzed using Analysis of Variance (ANOVA) and the Least Significant Difference (LSD) test at a 5% significance level.The ANOVA results showed that the different types of vegetables significantly affected feed consumption levels. The highest average percentage of feed weight reduction was found in lettuce leaves (61.2%) and cassava leaves (58.2%), followed by sweet leaf leaves (51.0%), mustard greens (47.2%), spinach leaves (46.9%), and the lowest was in water spinach leaves (43.5%). Lettuce leaves were preferred due to their soft texture and high moisture content, while cassava leaves were favored for their nutritional protein value. Conversely, spinach and water spinach leaves were less preferred due to antinutritional compounds (oxalic acid) and the rapid wilting nature of the leaves. The daily body weight growth of the crickets was directly proportional to the feed consumption rate. The study concludes that providing lettuce leaves and cassava leaves represents the most effective local alternative feed to maximize the body weight growth of the field cricket (Gryllus bimaculatus).